MANAJEMEN PROGRAM PEMBERDAYAAN MASYARAKAT MELALUI ALOKASI DANA DESA DI KENAGARIAN AIA MANGGIH KECAMATAN LUBUK SIKAPING - Hermawati Hermawati; Eliza Eliza; Serlita Utami (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
This paper is motivated by an increase in the activities of the community empowerment program from the previous year which prioritizes physical development, the allocation of village funds plays an important role in helping government, development and community empowerment at the village level. The implementation does not only involve village officials, but is open, mutual cooperation and involving all parties. This study aims to determine the management functions associated with community empowerment programs through the allocation of village funds in Kenagarian Aia M Sophisticated from planning, organizing, mobilizing and monitoring. The method used is a qualitative method with the data source of nagari guardians, community leaders and community members. Interview and documentation data collection techniques are processed by the step of data reduction, data presentation, and drawing conclusions. The first result is that planning for community empowerment programs starts from the jorong deliberations, the nagari deliberations, then the musrenbang is held for both physical and non-physical development activities. Second, the organization is marked by the existence of duties and responsibilities of each device, although it is still not optimal because there is still eg communication between village officials. Third, the application of actuating is still not optimal because there are still many people who have not been able to take part in the training because of funding and other activities occupied by the community. Fourth, supervision has been successful, but accountability and reporting are still not optimal